Moore's clinically oriented anatomy - Dalley, Arthur F., II; Agur, A. M. R.; Moore, Keith L. (Philadelphia : Wolters Kluwer, 2023)
"Clinically Oriented Anatomy is widely acclaimed for its comprehensive and well-written, "story-telling" text, accurate and detailed illustrations, and the relevance of its clinical correlations ("blue boxes"). The textbook serves as a complete reference and places clinical emphasis on anatomy that is important in physical diagnosis for primary care, interpretation of diagnostic imaging, and understanding the anatomical basis of emergency medicine and general surgery. This textbook is popular in a variety of programs, including medical, physician assistant, physical therapy, occupational therapy, graduate biology/anatomy, and exercise science"--
Overview and Basic Concepts -- Back -- Upper Limb -- Thorax -- Abdomen -- Pelvis and Perineum -- Lower Limb -- Head -- Neck -- Summary of Cranial Nerves.
Preceded by Clinically oriented anatomy / Keith L. Moore, Arthur F. Dalley II, Anne M. R. Agur. Eighth edition. [2018].
Includes bibliographical references and index.
Catalography
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Anatomy